Administration of Fenugreek Seed (Trigonella foenum-graecum Linn.) Ethanol Extract Reduces Spermatozoa Quality of Young Adult Mice (Mus musculus) - Susilawati, Putu; Satriyasa, Bagus Komang; Widianti, I Gusti Ayu (Metamorfosa: Journal of Biological Sciences, 2022)
This study aimed to determine the activity of the ethanol extract of Fenugreek Seed ( Trigonella foenum-graecum Linn.) to reduce the sperm quality of young adult mice ( Mus musculus ) as a natural male contraceptive. This research is an experimental study using a post-test only control group design. The sample of this study consisted of 36 male Swiss Webster ( Mus musculus ) mice aged 2-3 months with a body weight of 20-30 grams which were divided into two groups randomly. The control group (P 0 ) was given 0.5 ml of CMC Na 0.3% and the treatment group (P 1 ) was given the ethanol extract of Fenugreek Seed ( Trigonella foenum-graecum Linn.) 0.4 mg/gram BW as much as 0.5 ml for 36 day orally. The results showed that the administration of ethanol extract of Fenugreek Seed ( Trigonella foenum-graecum Linn.) could reduce the quality (concentration, motility, viability, and morphology) of spermatozoa (P?0.05), so that Fenugreek Seed ( Trigonella foenum-graecum Linn.) has potential as a natural male contraceptive.